When Government Speaks in Metaphor of Indonesian News: A Conceptual Metaphor Perspective and Translation - Ambarani, Ida Komang; Ni Luh Sherin Prihantana; Ni Nyoman Trisukarsih (Denpasar Institute, 2026)
This study aims to analyze the types of conceptual metaphor and translation of metaphor in the news of President Prabowo Subianto’s inaugural speech. This study used descriptive qualitative. The data were taken from Prabowo Subianto’s first speech in which Indonesian as the Source Language (SL) and English as Target Language (TL). The data were collected through content analysis, note-taking, and documentation. The data were analyzed by preparing and organizing the data, reducing the data, then representing the data in table and discussion. The result found that there are 6 structural metaphors and 1 ontological metaphor. Additionally, 5 data used reproducing the same image in TL, 1 used deleting metaphor and 1 replacing SL image into TL image are translation metaphors used in this data.